2014
DOI: 10.1177/000313481408001223
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of Lower Urinary Tract Injury after Gastrointestinal Surgery in the Nationwide Inpatient Sample Database

Abstract: Bladder and ureteral injury are serious iatrogenic complications during abdominal and pelvic surgery but are poorly investigated in the general surgery literature. The objective of this study was to examine rates, trends, and patient and surgical characteristics present in lower urinary tract injuries during gastrointestinal surgery using the Nationwide Inpatient Sample (NIS) database. The NIS database was queried from 2002 to 2010 for gastrointestinal surgery procedures including small/large bowel, rectal sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 17 publications
0
12
0
Order By: Relevance
“…The presence of 3 cases of urinary bladder injury is of the most relevant consideration [30,31]. There is, obviously, nothing reported of this complication in open liver surgery and only some series of laparoscopic pelvic surgery report data on bladder injuries but all of them during the surgical procedure [34,35]. Gynaecological procedures describe up to 8% of iatrogenic bladder injuries [34] whilst in general surgery procedures such as bowel resections (including rectal resection), it occurred between 0.12 and 0.41% [35].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of 3 cases of urinary bladder injury is of the most relevant consideration [30,31]. There is, obviously, nothing reported of this complication in open liver surgery and only some series of laparoscopic pelvic surgery report data on bladder injuries but all of them during the surgical procedure [34,35]. Gynaecological procedures describe up to 8% of iatrogenic bladder injuries [34] whilst in general surgery procedures such as bowel resections (including rectal resection), it occurred between 0.12 and 0.41% [35].…”
Section: Discussionmentioning
confidence: 99%
“…There is, obviously, nothing reported of this complication in open liver surgery and only some series of laparoscopic pelvic surgery report data on bladder injuries but all of them during the surgical procedure [34,35]. Gynaecological procedures describe up to 8% of iatrogenic bladder injuries [34] whilst in general surgery procedures such as bowel resections (including rectal resection), it occurred between 0.12 and 0.41% [35]. Robotic liver surgery therefore might represent an increment in the rate of urinary bladder injuries and this data needs to be confirmed.…”
Section: Discussionmentioning
confidence: 99%
“…They also found metastatic disease to be significantly associated with elevated risk of ureteral injury. 10 Yet another retrospective review of a single institution's experience with colorectal surgery found an increased incidence of ureteral injury with laparoscopic versus open surgery (0.66 vs. 0.15%, p ¼ 0.007). 11 As can be seen from these studies, the relationship of surgical modality and ureteral injury is not clear.…”
Section: Ureteral Injuries Risk Factorsmentioning
confidence: 99%
“…Ureteric injury is a recognized complication of abdominal surgery which involves mobilization of the large bowel . The incidence of colo‐ureteric fistulae after bowel surgery is extremely rare.…”
mentioning
confidence: 99%